Synthesis, characterization, and photocatalytic performance of a ternary composite catalyst α-SiW11Cr/PANI/ZnO. Issue 2 (17th January 2020) - Zhang, Cheng-Li; Ma, Rong-Hua; Yang, Ming-Rui; Cao, Rui; Wen, Qi
Abstract: Wastewater from the printing and dyeing industry is an area of growing concern. Photocatalysts synthesized using polyaniline (PANI) and certain metal oxides have been increasingly used for the purpose owing to their high photocatalytic potential, ease of synthesis, and ease of recycle and reuse. Herein, a ternary composite α-SiW11Cr/PANI/ZnO was prepared by electrostatic self-assembly, and characterized by infrared (IR) spectroscopy, diffraction of X-rays, scanning electron microscopy, etc. N2 adsorption-desorption showed that the composite had a bimodal pore system for mesoporous materials. Catalytic activity of α-SiW11Cr/PANI/ZnO for photodegradation of organic dye malachite green under UV irradiation was studied. Compared with single materials, ternary composites have better photocatalytic performance. Graphical Abstract: